2018
DOI: 10.1186/s12885-018-4041-2
|View full text |Cite
|
Sign up to set email alerts
|

HtrA1 as a promising tissue marker in cancer: a meta-analysis

Abstract: BackgroundHtrA1 is expressed in a variety of normal human tissues and seems to be involved in numerous physiological processes as well as tumorigenesis. This study reports the results of a meta-analysis that was performed: to compare HtrA1 expression as mRNA and protein, in cancer tissue versus non-cancer tissue and to assess overall survival in relation to low or medium-high HtrA1 tissue expression.MethodsThe PRISMA method was used for study selection. OR and HR with 95% confidence interval was used as a meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…HtrA1 belongs to the serine protease family, and its deficient expression has been reported in several human cancers, such as pancreatic cancer [20], breast cancer [21], and hepatocellular carcinoma [22]. HtrA1 can suppress malignant development and progression of cancer [23], and it also has been reported to be involved in chemotherapy resistance. For example, Xu et al reported that loss of HtrA1 expression can induce cancer stem cell-like properties of lung adenocarcinoma cells, leading to resistance to cisplatin treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…HtrA1 belongs to the serine protease family, and its deficient expression has been reported in several human cancers, such as pancreatic cancer [20], breast cancer [21], and hepatocellular carcinoma [22]. HtrA1 can suppress malignant development and progression of cancer [23], and it also has been reported to be involved in chemotherapy resistance. For example, Xu et al reported that loss of HtrA1 expression can induce cancer stem cell-like properties of lung adenocarcinoma cells, leading to resistance to cisplatin treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…HtrA2 is located in the mitochondrial intermembrane space where it contributes to mitochondrial homeostasis and protects against cellular stress under normal physiological conditions [11,12]. Once apoptosis is triggered, HtrA2 is released into the cytosol, where it binds to and degrades apoptotic factors, such as XIAP and CIAP1/2 [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…HtrA2, which does not contain such a domain, participates in cell apoptosis to ensure the physiological turnover of trophoblasts and in this way affects pregnancy outcome [8][9][10]. HtrA2 is located in the mitochondrial intermembrane space where it contributes to mitochondrial homeostasis and protects against cellular stress under normal physiological conditions [11,12]. Once apoptosis is triggered, HtrA2 is released into the cytosol, where it binds to and degrades apoptotic factors, such as XIAP and CIAP1/2 [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%